STRUKTURAL ANALISIS MODEL PROSES PEMBELAJARAN DENGAN PENDEKATAN KEPUASAN LULUSAN: STUDI KASUS PADA TRACER STUDY PROGRAM STUDI ADMINISTRASI BISNIS - Andi - Setiawan; Suwardi Suwardi; Khairul Saleh; Suharmanto Suharmanto (Admisi dan Bisnis, 2019)
The current study was conducted to increase of our understanding of factors that influence distinctiveness of the curriculum as efforts to maintain and improve the quality of education in study program graduate of Business Administration. An extensive review of the existing literature was used to identify 32 factors that Affect quality of education and Alumni satisfaction. Data or a questionnaire distributed to 133 graduates study program graduate of Business Administration Department of Business Administration Polytechnic State Semarang. Of the 133 questionnaires distributed were returned as many as 124, and 9 questionnaires are not returned by the target date. The analysis of 124 questionnaires there are 13 questionnaires that occurred outlier. So the data or questionnaires that can be used for the study were as many as 111 questionnaires. Results from both the qualitative and quantitative phases of the current study demonstrated that 32 factors that Affect quality of education and Alumni satisfaction can be clustered into three basic process. First, based on the results of data analysis showed that the acquisition of specialized expertise is the key or most dominant variable, Second, results demonstrate mastery of tools and technology are the two variables that affect the realization of graduate satisfaction. Third, the results of data analysis showed that the formation of character and behavior of the third element in increasing the satisfaction of graduates through the value of the learning process The sectors in which the alumni study program graduate of Business Administration were not completely representative of reviews their year of graduation and geographical region.  The findings suggest that, in order to increase of satisfaction study program graduate of Business Administration, Then focus on mastery of special skills is the most dominant variable that can affect the value of the learning process, This is a strength study program graduate of Business Administration, then the advice and recommendation is to maintain and emphasize the element of learning output is -unsur formed on the entire course, which relate directly and indirectly to the mastery of special skills in administration. This study contributes to the body of knowledge on the value of the learning process.